The study of spiritual health of aged volunteers in Taiwan - Hung, Ying-tsun; Li, Ming-fen; Chiu, Yu-chiu (2010)
Spirituality plays a vital role in determining the state of well-being of the elderly. The purpose of this study was to explore the spiritual health of aged volunteers in Taiwan. Methods: Twelve aged volunteers were interviewed. They are 6 male and 6 female, age range 60 to 85 years.Data were analyzed using thematic analysis. Results: The results of this study was that from social services, the aged volunteers learned to open their mind and no so attached. Through helping others,they interconnected to foster their spiritual health. From helping others, they fell that they are so lucky, and become more grateful, joyful, peaceful. In their later life, they found their meaning in life. Religion play important role for aged volunteers, through religion belief, they became more aggressive doing social services. Conclusions: The aged volunteers did social services by supported family members. From volunteer services, they enhanced spiritual health and live more meaningful and grateful.